Pengaruh Customer Relationship Marketing dan Customer Value terhadap Loyalitas Pelanggan Barista Coffe Shop & Roastery Tanjungpinang - Iranita, Iranita (Program Studi Manajemen FEBM UMRAH, 2022)
The results of this study aim to determine the effect of relationship marketing and customer value on customer loyalty Barista Coffee Shop & Roastery Tanjungpinang. The population used in this study are all consumers who have visited or consumed more than 2 times the products at Tanjung Pinang Barista Coffee Shop & Roastery. Determination of the sample in this study using the method of Accidental Sampling is a sampling technique based on chance meeting with a number of criteria that are tailored to the purpose of the study so that 96 respondents were selected who met the criteria and were involved in this study by filling out a questionnaire that had been distributed. Data analysis using multiple linear regression, including t test, F test and coefficient of determination. The results showed that relationship marketing and customer value to customer loyalty Barista Coffee Shop & Roastery Tanjungpinang. The results of this study indicate that the Relationship Marketing variable has a positive and significant effect on customer loyalty, the Customer Value variable has a positive and significant effect on customer loyalty. Based on the results of simultaneous testing of relationship marketing variables, customer value has a positive and significant effect on customer loyalty. The results of this study can be a reference for the Tanjungpinang area to make Tanjungpinang a citybranding of culinary service providers.